Perbandingan Biaya dan Waktu Pekerjaan Drainase Antara Box Culvert 150×150 cm dan Plat Duiker pada Jalan Raya Simpang Lebong Kecamatan Curup Kabupaten Rejang Lebong - Niki Satrianda; Rezi Munizar (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Road drainage development is an essential aspect of supporting sustainable transportation infrastructure, particularly in areas with high rainfall intensity and heavy traffic conditions. This study aims to compare the cost and implementation time of drainage works using a 150×150 cm Box Culvert and a Plat Duiker method on Simpang Lebong Road, Curup District, Rejang Lebong Regency. The research employed a descriptive quantitative method through comparative analysis of construction costs, implementation characteristics, field conditions, and construction effectiveness. The results indicate that the Box Culvert method provides advantages in structural strength, water flow capacity, and installation time efficiency, while the Plat Duiker method offers lower initial construction cost potential. Under conditions of continuous existing water flow, high rainfall intensity, and dense traffic activity, the Box Culvert method is considered more effective due to its ability to minimize construction disturbances and improve drainage system reliability.